Evaluation of the antispasmodic and antioxidant activities of an alkaloid extracted from Pancratium foetidum Pom. (Moroccan Endemic Amaryllidaceae) - Bendaif Hajar; Melhaoui Ahmed; Elouadi Yassir; Essadki Samia; Elmsellem Hicham; Benali Taoufiq; Aziz Mohammed; Hafez Baraa; Hachmi Azeddine; Abrigach Farid (E3S Web of Conferences)
Lycorine is a natural alkaloid extracted from the Amaryllidaceae plant family. It has been reported to exhibit a wide range of physiological effects, including the potential effect against cancer. The antispasmodic activity was investigated in vitro using rabbit intestine, and the antioxidant activity was evaluated by DPPH assay. The results indicated that lycorine has an irreversible relaxant property on the isolated rabbit jejunum. Whereas, it did not show a significant antioxidant activity toward the DPPH free radical in comparison with ascorbic acid.